2021
DOI: 10.1002/smll.202101323
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Structure and Frustrated Magnetism in High Entropy Rare‐Earth Zirconates

Abstract: The configurational complexity and distinct local atomic environments of high entropy oxides remain largely unexplored, leaving structure‐property relationships and the hypothesis that the family offers rich tunability for applications ambiguous. This work investigates the influence of cation size and materials synthesis in determining the resulting structure and magnetic properties of a family of high entropy rare‐earth zirconates (HEREZs, nominal composition RE2Zr2O7 with RE = rare‐earth element combinations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 52 publications
0
16
0
Order By: Relevance
“…Limited work has been reported on nano-HEOs to date. Wang et al 17 18 Nebulized spray pyrolysis, flame spray pyrolysis, and reverse co-precipitation techniques were employed by Sarkar et al to synthesize nanocrystalline rock salt structure HEOs. 19,20 Lowtemperature solvothermal synthesis with pyrolysis at 400 °C was developed for obtaining nano-spinel structure HEOs by Wang et al, 21 and the sol−gel method was used by Wang et al to fabricate nano-spherical mesoporous spinel HEO particles.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Limited work has been reported on nano-HEOs to date. Wang et al 17 18 Nebulized spray pyrolysis, flame spray pyrolysis, and reverse co-precipitation techniques were employed by Sarkar et al to synthesize nanocrystalline rock salt structure HEOs. 19,20 Lowtemperature solvothermal synthesis with pyrolysis at 400 °C was developed for obtaining nano-spinel structure HEOs by Wang et al, 21 and the sol−gel method was used by Wang et al to fabricate nano-spherical mesoporous spinel HEO particles.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Wang et al reported a nano-HEO material (Cu–Cr–Fe–Co–Ni–O) obtained via laser scanning ablation. The preparation of nano-fluorite HEO materials with ball-milling, chemical co-precipitation, and polymeric steric entrapment was reported by Jothi et al Nebulized spray pyrolysis, flame spray pyrolysis, and reverse co-precipitation techniques were employed by Sarkar et al to synthesize nanocrystalline rock salt structure HEOs. , Low-temperature solvothermal synthesis with pyrolysis at 400 °C was developed for obtaining nano-spinel structure HEOs by Wang et al., and the sol–gel method was used by Wang et al to fabricate nano-spherical mesoporous spinel HEO particles . We note that materials in these works have been reported as nano-HEOs (not nano-CCOs), though most do not explore/discuss specific thermodynamic criteria distinguishing them one way or the other.…”
Section: Introductionmentioning
confidence: 99%
“…Large variation in local chemical environments have also been shown to lead to useful magnetic properties. For example, compositionally complex alloys, intermetallics, and oxides have been shown to have intriguing magnetic properties [15][16][17][18]. There is significant interest in leveraging these intriguing features to design novel magnets with low coercivity and high saturation magnetization (M s ) [19].…”
Section: Introductionmentioning
confidence: 99%
“…Although complex magnetic behaviors have been reported in HEOs , such as perovskites, pyrochlores, spinels, zirconates, and Ruddlesden–Popper oxides, so far, only some of them were able to offer magnetic details, such as long-range magnetic order or magnetic phase competition, for example. For a rock salt-type (Co, Cu, Mg, Ni, and Zn)O structure, an antiferromagnetic (AFM) order has been predicted from modeling experiments, which could be confirmed by magnetic susceptibility as well as neutron diffraction below a critical temperature of ∼120 K. , Moreover, the short-range spin ordering in its glassy magnetization state can be tuned by ∼65% by changing the Cu amount from 11 to 27% .…”
Section: Introductionmentioning
confidence: 99%